STUDI FENOMENOLOGI: PENGALAMAN PASIEN KANKER STADIUM LANJUT YANG MENJALANI KEMOTERAPI - Utami, Gamya Tri; Wahyuni, Dwi '; Huda, Nurul ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Insidence of cancer have a increased every year. Almost case of cancer finded in late stage cancer caused by delay treatment. Patient with late stage cancer have low survival year live. Treatment can be given in late stage cancer with existence of metastase process was paliatif care. The principle purpose of treatment focused to increase the quality of live and minimization symptom of cancer. This research was qualitative design with descriptive phenomenology method. The aim was to exploration the experienced of patient with late stage cancer who undergoing chemotherapy. The result was identified six themes, there are: 1) knowledge about chemotherapy, 2) side effect of chemotherapy, 3) coping during treatment, 4) support of family, 5) performance of nurse and 6) hopes to nurse. This result expected to nurse can gives information to understand the patient late stage cancer who undergoing chemotherapy. Nurse can give quality of paliatif care with caring attitude. Keywords: Cancer last stage, chemotherapy, phenomenology study